ESIPT of 1-[N-(2-Pyridyl) Aminomethylidene]-2(1H)-Naphtalenone: A TDDFT Study (Journal of Atomic and Molecular Sciences, 2022)
In the present work, the excited state intramolecular proton transfer (ESIPT)process between the Enol and Keto forms of the title compound has been investigatedwith the time-dependent density functional theory (TDDFT) method. The geometricstructures, frontier molecular orbitals, electrostatic potential (ESP) maps as well asthe absorption and fluorescence spectra of the two forms of the title compound havebeen investigated. The calculated absorption spectra of the Keto form are more inagreement with the experimental results. Moreover, the potential energy curves of theintramolecular proton transfer (IPT) within the title compound have been scanned inboth ground state $S_0$ and the first excited state $S_1.$ We found that the intramolecularproton transfer from Enol form to Keto form in excited state is almost barrierless withan energy barrier 2.1 kJ/mol whereas intramolecular proton transfer between the twoforms of the title compound in ground state is forbidden with energy barrier as highas 10.5 kJ/mol.
Keywords: Intramolecular hydrogen bonding; ESIPT; Frontier molecular orbitals; Electronic spectra; Potential energy curves.